CONSTITUTIONAL PROPERTY: A HISTORICAL AND POLITICAL APPROACH TO PROPERTY RIGHTS IN BRAZIL - Bezerra, Matheus Ferreira (2024)
The present work proposes to carry out a historical study on property, from a perspective on the property and not only on the functions or powers of the owner, in order to understand its legitimization process over the years, and the transformations undergone, relating these changes to the effects promoted in property rights, in particular, Brazilian law, based on a comparison between the provisions provided for by the civil codes of each moment. This work proposal aims to understand the political role attributed to property, at each historical moment, in order to understand its role in society, based on the understanding that it has a function inherent to its existence, as it is legitimized from political choices. In this sense, through a vision contextualized with the current proposal, brought by the Federal Constitution of 1988, with its principles and values, the work seeks a reflection on the inherent function of property.